2016
DOI: 10.2147/opth.s117372
|View full text |Cite
|
Sign up to set email alerts
|

Corneal stromal demarcation line after collagen cross-linking in corneal ectatic diseases: a review of the literature

Abstract: Collagen cross-linking (CXL) is a relatively new conservative approach for progressive corneal ectasia, which is able to strengthen corneal tissue reforming new covalent bonds. Subjective and objective results following this method seem to be promising. In recent years, newer CXL protocols have been developed to perform more effective and less invasive procedures. The increasing diffusion of CXL in the corneal ectatic disease has increased the need to have actual indices regarding the efficacy of the treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 66 publications
1
29
0
Order By: Relevance
“…Brittingham et al (2014) stated that AXL has negative effect on the demarcation line at 12 months after cross-linking with increased steepening of the anterior corneal surface. Spadea et al (2016) reported that the depth of the stromal demarcation line after standard CXL ranged from 300 to 500 lm while in pulsed AXL about 210 lm and only about 150 lm in continuous mode AXL. Mazzotta et al evaluated the qualitative micromorphological postoperative outcomes of the cornea following AXL using confocal microscopy.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Brittingham et al (2014) stated that AXL has negative effect on the demarcation line at 12 months after cross-linking with increased steepening of the anterior corneal surface. Spadea et al (2016) reported that the depth of the stromal demarcation line after standard CXL ranged from 300 to 500 lm while in pulsed AXL about 210 lm and only about 150 lm in continuous mode AXL. Mazzotta et al evaluated the qualitative micromorphological postoperative outcomes of the cornea following AXL using confocal microscopy.…”
Section: Discussionmentioning
confidence: 98%
“…Spadea et al. () reported that the depth of the stromal demarcation line after standard CXL ranged from 300 to 500 μ m while in pulsed AXL about 210 μ m and only about 150 μ m in continuous mode AXL. Mazzotta et al.…”
Section: Discussionmentioning
confidence: 99%
“…The concept ‘the deeper, the better’ in evaluating efficacy in CXL treatment has been discussed in a recent paper (Spadea et al. ). The present study supports this concept.…”
Section: Discussionmentioning
confidence: 99%
“…[64][65][66][67][68] Demarcation line is a transition zone between the crosslinked anterior corneal stroma and the untreated posterior corneal stroma. [64][65][66][67][68] Demarcation line is a transition zone between the crosslinked anterior corneal stroma and the untreated posterior corneal stroma.…”
Section: Demarcation Linementioning
confidence: 99%
“…There is evidence in the literature emphasizing that demarcation line could be a measure of effectiveness of CXL. [64][65][66][67][68] Demarcation line is a transition zone between the crosslinked anterior corneal stroma and the untreated posterior corneal stroma. It is considered as a marker of depth of CXL treatment into the stroma.…”
Section: Demarcation Linementioning
confidence: 99%